Eksplorasi Etnomatematika Pada Ornamen Islam Gedung Universitas Islam Negeri Mataram - Magfirah, Siti; Pardi, Habib Husnial (Mathematic Education Departement, State Islamic University of Mataram, 2024)
The aim of this research is to determine the ethnomathematics elements in the Islamic ornament design of building B FTK UIN Mataram. This research is a type of qualitative descriptive research. Data on ethnomathematics elements in the Islamic ornament design of building B FTK UIN Mataram was taken using observation and documentation techniques. The object in this research is the Islamic ornaments of building B FTK UIN Mataram. All data were analyzed using qualitative descriptive with the Miles and Huberman model. The results of the research are that there are ethnomathematics aspects in the Islamic ornaments of building B, Faculty of Tarbiah and Teacher Training, Mataram State Islamic University. This can be seen from the geometric concepts of flat shapes and spatial shapes such as rectangles, hexagons, hexagrams, blocks and tubes. Then there are the concepts of transformation geometry such as translation, reflection and rotation